Atomistic modeling of the Ti-Al binary system - Kim, Young-Kwang; Kim, Hong-Kyu; Jung, Woo-Sang; Lee, Byeong-Joo (ELSEVIER SCIENCE BV, 2016)
An interatomic potential for the Ti-Al binary system has been developed based on the second nearest-neighbor modified embedded-atom method (2NN MEAM) formalism. This potential describes fundamental materials properties (structural, thermodynamic, elastic, defect, deformation and thermal properties) of Ti-Al alloys in good agreements with experimental or first-principles data. The transferability and applicability of the present potential to atomic-scale investigations for Ni-based superalloys or Ti-Al based alloys are demonstrated. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: CRYSTAL ELASTIC-CONSTANTS; STACKING-FAULT ENERGIES; PHASE-STABILITY; 1ST-PRINCIPLES CALCULATIONS; INTERATOMIC POTENTIALS; ELECTRONIC-STRUCTURE; TI3AL; INTERMETALLICS; ALLOYS; FRACTURE